EL CAPITAL HUMANO Y LA POBREZA: ESTUDIO DE SU RELACIÓN A NIVEL CANTONAL EN ECUADOR EN EL PERÍODO 2007-2016 - Peñarreta Cabrera, Jenny Marisol (2019)
Poverty is a phenomenon of great importance in society, it has been reduced by the scarcity of goods and services that are essential in families, it can persist throughout life and is repeated from generation to generation. Faced with this problem was raised as a research topic: "Human capital and poverty: study of a relationship at the cantonal level in Ecuador in the period 2007-2016." Whose general objective is: to evaluate the ratio of human capital measured by years of schooling in the cantons of Ecuador, period 2007-2016, through the use of a descriptive analysis, using panel data techniques and spatial techniques for the purpose of establishing The incidence of human capital on income poverty 214 cantons of Ecuador classified by the level of non-petroleum Gross Aggregate Value in the panel model and 166 cantons in the spatial model. The information comes from the National Survey of Employment, Unemployment and Underemployment (ENEMDU, for its acronym in English) for the period 2007-2016. The main results are manifested in a range of -1,6% and -4,4%. Finally, with the spatial panel data models, the spatial dependence was confirmed in the SAR, SEM and SAC models. An implication of economic policy derived from the results that should improve the quality of education, especially in rural sectors.